Effect of Seminal Plasma Protein Fractions on Stallion Sperm Cryopreservation - Bubenickova, Filipa; Postlerova, Pavla; Simonik, Ondrej; Sirohi, Jitka; Sichtar, Jiri (International journal of molecular sciences, 2020)
Seminal plasma (SP) is the natural environment for spermatozoa and contains a number of components, especially proteins important for successful sperm maturation and fertilization. Nevertheless, in standard frozen stallion insemination doses production, SP is completely removed and is replaced by a semen extender. In the present study, we analyzed the effects of the selected seminal plasma protein groups that might play an important role in reducing the detrimental effects on spermatozoa during the cryopreservation process. SP proteins were separated according to their ability to bind to heparin into heparin-binding (Hep+) and heparin-non-binding (Hep-) fractions. The addition of three concentrations-125, 250, and 500 µg/mL-of each protein fraction was tested. After thawing, the following parameters were assessed: sperm motility (by CASA), plasma membrane integrity (PI staining), and acrosomal membrane integrity (PNA staining) using flow cytometry, and capacitation status (anti-phosphotyrosine antibody) using imaging-based flow cytometry. Our results showed that SP protein fractions had a significant effect on the kinematic parameters of spermatozoa and on a proportion of their subpopulations. The 125 µg/mL of Hep+ protein fraction resulted in increased linearity (LIN) and straightness (STR), moreover, with the highest values of sperm velocities (VAP, VSL), also this group contained the highest proportion of the fast sperm subpopulation. In contrast, the highest percentage of slow subpopulation was in the groups with 500 µg/mL of Hep+ fraction and 250 µg/mL of Hep- fraction. Interestingly, acrosomal membrane integrity was also highest in the groups with Hep+ fraction in concentrations of 125 µg/mL. Our results showed that the addition of protein fractions did not significantly affect the plasma membrane integrity and capacitation status of stallion spermatozoa. Moreover, our results confirmed that the effect of SP proteins on the sperm functionality is concentration-dependent, as has been reported for other species. Our study significantly contributes to the lack of studies dealing with possible use of specific stallion SP fractions in the complex puzzle of the improvement of cryopreservation protocols. It is clear that improvement in this field still needs more outputs from future studies, which should be focused on the effect of individual SP proteins on other sperm functional parameters with further implication on the success of artificial insemination in in vivo conditions.
Keywords: cryobiology; Male; Serum Globulins; Cryopreservation; biotechnology; Spermatozoa; mužské pohlaví; lidský sérový albumin; artificial insemination; Semen Preservation; uchování spermatu; proteiny semenné plazmy; Seminal Plasma Proteins; Animals; phosphorylation; zvířata; spermie; koně; sérové globuliny; Serum Albumin, Human; kryoprezervace; Horses; spermatozoa